ERROR ANALYSIS IN SOLVING STRAIGHT MOTIONS' PROBLEMS OF SENIOR HIGH SCHOOL STUDENTS IN PEKANBARU - Vetty Vellancia; Zulirfan Zulirfan; Hendar Sudrajad (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2019)
Errors are deviations from things that have been known to be true, errors by students in solving problems can be used by the teacher as a tool in knowing the extent of student ability, so that it can be known the difficulties experienced by students in the learning process. The purpose of this research is to describe the types of errors made by students in solving physics problems on straight motion material at SMAN 5 Pekanbaru. Population in this research were 360 students of class X SMAN 5 Pekanbaru. Samples were taken randomly and a total of 72 students were obtained. This research instrument was in the form of essay questions which were arranged based on the types of errors commonly made by students. Data was collected by giving essay test questions to the research sample. Data analysis in this research uses descriptive analysis with percentage techniques, which provide an overview of the level of errors made by students. Using the six questions that were tested, the most dominant type of error was obtained by students, namely the types of concept errors and data calculation errors, while the types of errors that were least experienced by students were the types of mathematical errors. For this reason, in learning physics on the topic of GLBB in class X SMA N 5 Pekanbaru, it is necessary to emphasize understanding of concepts and calculation of data that is more optimal so that students get better learning outcomes.